2013
DOI: 10.1111/1756-185x.12095
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the clinical examination for detecting Baker's cyst in asymptomatic fossa

Abstract: This study demonstrates that many patients may have BCs without any symptoms at the popliteal fossa and clinical examination of the popliteal fossa could not accurately detect BC. US examination of the popliteal fossa should be performed to detect BCs and this may recover the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…A total of five patients in this group (0.7%) had a ruptured Baker’s cyst on USS. The prevalence of Baker’s cysts is higher in this study compared to other studies, with the prevalence of Baker’s cysts reported between 7% and 30% 1423 (see Table 3). Patients in these studies were predominantly Rheumatology patients or patients with knee pain assessing the diagnosis and management of knee OA.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…A total of five patients in this group (0.7%) had a ruptured Baker’s cyst on USS. The prevalence of Baker’s cysts is higher in this study compared to other studies, with the prevalence of Baker’s cysts reported between 7% and 30% 1423 (see Table 3). Patients in these studies were predominantly Rheumatology patients or patients with knee pain assessing the diagnosis and management of knee OA.…”
Section: Discussioncontrasting
confidence: 71%
“…Baker's cysts are benign, synovial-lined cysts arising from the posterior knee joint and are a consequence of underlying knee joint OA. 14 On imaging, they characteristically extend into the popliteal fossa from the knee joint, between the medial head of the gastrocnemius and semimembranosus muscles. 1 The most common clinical finding is a smooth swelling behind the knee that may or may not be painful.…”
Section: Discussionmentioning
confidence: 99%
“…59 In the B-mode, BC appear as fluid-filled swellings on the posterior side of the knee (Figure 5B). 60 In addition, during a 2-year follow-up, ultrasound evidence of BC has been shown to predict the clinical and radiological progression of KOA. 61 Hoffa Fat Pad One function of the Hoffa Fat Pad (HFP) is to absorb impulsive actions generated through the knee joint, whereas it loses proper stress-strain behavior under mechanical loads in KOA conditions.…”
Section: Osteophytesmentioning
confidence: 99%
“…In the B‐mode, BC appear as fluid‐filled swellings on the posterior side of the knee (Figure 5B). 60 In addition, during a 2‐year follow‐up, ultrasound evidence of BC has been shown to predict the clinical and radiological progression of KOA 61 …”
Section: Structural Findingsmentioning
confidence: 99%
“…BC has demonstrated a longitudinal association with the radiological and clinical progression of osteoarthritis [ 8 ] and may therefore be considered a predictor of osteoarthritis [ 9 ] and a modifiable treatment target [ 10 ]. Early diagnosis of BC may prevent further complications connected with the direct compression or ruptures to the surrounding tissues [ 11 ]. However, it may be a challenging task for physicians to differentiate BC from other musculoskeletal disorders in or near the popliteal fossa, such as synovial and bone tumor, meniscal cyst and ganglion cyst, which share similar symptoms and signs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%